Hoxb5 marks long-term haematopoietic stem cells revealing a homogenous perivascular niche - Chen, James Y. (Nature, 2016)
The hematopoietic stem cell (HSC) is arguably the most extensively characterized tissue stem cell. Since its identification by prospective isolation(1), complex multi-parameter flow cytometric isolation of phenotypic subsets has facilitated studies on many aspects of HSC biology including, self-renewal(2–4), differentiation, aging, niche(5), and diversity(6–8). Here we demonstrate by unbiased multi-step screening, identification of a single gene, Hoxb5 (homeobox B5 also known as Hox-2.1), whose expression in the bone marrow (BM) is limited to the long-term HSC (LT-HSC) in mice. Utilizing a single-color tri-mCherry reporter mouse driven by endogenous Hoxb5 regulation, only the Hoxb5-positive HSCs exhibit long-term reconstitution capacity after transplantation in primary transplant recipients, and critically, in secondary recipients. Only 7–35% of various previously defined immunophenotypic HSCs are LT-HSCs. Finally, by in situ imaging of mouse BM, we show that >94% of LT-HSC (Hoxb5(+)) are directly attached to VE-cadherin-positive cells, implicating a perivascular space as a near homogenous localization of the LT-HSC.